2016
DOI: 10.2340/00015555-2329
|View full text |Cite
|
Sign up to set email alerts
|

Economic Burden of Psoriasis and Potential Cost Offsets with Biologic Treatment: A Swedish Register Analysis

Abstract: Estimates of direct and indirect costs of psoriasis are limited. The aim of this study was to estimate: (i) costs in patients with psoriasis compared with controls; and (ii) impact on costs from initiating biologics. The study extracted data from Swedish administrative registers and compared 31,043 patients with 111,645 sex-, age- and residency-matched referents. Mean direct and indirect costs were estimated as US dollars (USD) 1,365 (62%) and USD 3,319 (50%) higher in patients compared with referents, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…Psoriasis may have major impact on everyday life, and there is evidence that individuals with psoriasis may die at younger ages (Abuabara et al, 2010;Gelfand et al, 2007;Stern et al, 2004). The Global Burden of Disease Study (Murray et al, 2015) reported that psoriasis made up a substantial part (0.19%) of the total global disability-adjusted life-years, and yearly costs due to treatment and loss of work are high (Feldman et al, 2014;Svedbom et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis may have major impact on everyday life, and there is evidence that individuals with psoriasis may die at younger ages (Abuabara et al, 2010;Gelfand et al, 2007;Stern et al, 2004). The Global Burden of Disease Study (Murray et al, 2015) reported that psoriasis made up a substantial part (0.19%) of the total global disability-adjusted life-years, and yearly costs due to treatment and loss of work are high (Feldman et al, 2014;Svedbom et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis, which is a chronic, inflammatory skin disorder, widely affects up to 2%‐4% of the world's population and severely impairs patient quality of life . The psoriasis skin lesions are characterized by hyperproliferation and aberrant differentiation of keratinocytes and infiltration of inflammatory cells into the dermis and epidermis …”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis, which is a chronic, inflammatory skin disorder, widely affects up to 2%-4% of the world's population [1] and severely impairs patient quality of life. [2][3][4] The psoriasis skin lesions are characterized by hyperproliferation and aberrant differentiation of keratinocytes and infiltration of inflammatory cells into the dermis and epidermis. [5] Although the pathogenesis of psoriasis is unclear, epidermal hyperplasia is found to be mediated by psoriasis-associated genes and the signalling pathways, such as the IL-23/Th17 axis, [6,7] the signal transducers and activators of transcription (STAT) signalling pathway [8,9] and the NF-ΚB signalling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…A recent Swedish study showed increased direct cost (+1,365 USD) and indirect costs (+ 3,319 USD) per patient with psoriasis per year, compared with the general population. If treated with biologicals, the high direct cost of medication (+ 23,293 USD per patient per year) was only partially offset by savings in indirect costs [ 10 ].…”
Section: Introductionmentioning
confidence: 99%